Produto potencial como ferramenta de análise da política monetária e da capacidade de crescimento da economia brasileira - José Ronaldo de Castro Souza Júnior; Sidney Martins Caetano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– It is proposed to estimate two versions of the potential output for Brazil in the period 1992-2010, through the production function and the HP filter, and use these results to: i) assess the relevance of the output gap in the monetary policy decisions (comparing the two estimates); and ii) to analyze sources of growth of potential output. The estimated production function indicates that the low productivity growth may have been a major contributor to the low growth potential of the country. Estimates indicate that it was not possible to achieve rates of potential output growth above 4% a.a. When considering the influence of the output gap in the reaction function of monetary authority, it appears that both measures generate similar performance. Therefore, if the analyst seeks only to measure the variation of the output gap, the HP filter may be more appropriate given its methodological simplicity.
Keywords: E01; E20; E30; O4; 330; potential output; output gap; monetary policy; economic growth and aggregate productivity